TANGGUNG JAWAB PRODUSEN PESAWAT UDARA TERHADAP KECELAKAAN PESAWAT BERDASARKAN HUKUM UDARA INTERNASIONAL - Imanika Srimulyandari; Muh. Risnain; Diva Pitaloka (Mataram Journal of International Law, 2025)
This research aims to analyze the form and application of responsibility carried out by manufacturers to the families of victims of aircraft accidents based on international air law. This research examines the cases of Boeing 737 Max, Airbus Helicopters EC130 B4, and F-35 Lightning II, all of which show design defect, manufacturing defect, and failure to warn. The research method used is normative law with a conceptual, international agreements, statute and case approach. Data was collected from primary, secondary, and tertiary legal materials including the results of accident investigation reports and other supporting data. The results show that producer responsibility has not been regulated directly in international air law such as the 1999 Montreal Convention, therefore the lawsuit relies on the principles of product liability and strict liability in the national legal system, especially the United States, so that there is a legal gap that creates legal uncertainty for parties who feel harmed by an aircraft accident. This study considers the need for international air law reform that includes aircraft manufacturers as parties who should be held liable for aircraft accidents to ensure international aviation safety and victim protection.